Catatonia - Hirjak, Dusan; Rogers, Jonathan P.; Wolf, Robert Christian; Kubera, Katharina Maria; Fritze, Stefan; Wilson, Jo Ellen; Sambataro, Fabio; Fricchione, Gregory; Meyer-Lindenberg, Andreas; Ungvari, Gabor S.; Northoff, Georg (Nature reviews. Disease Primers, 2024)
Catatonia is a neuropsychiatric disorder characterized by motor, affective and cognitive-behavioural signs, which lasts from hours to days. Intensive research over the past two decades has led to catatonia being recognized as an independent diagnosis in the International Classification of Diseases, 11th Revision (ICD-11) since 2022. Catatonia is found in 5-18% of inpatients on psychiatric units and 3.3% of inpatients on medical units. However, in an unknown number of patients, catatonia remains unrecognized and these patients are at risk of life-threatening complications. Hence, recognizing the symptoms of catatonia early is crucial to initiate appropriate treatment to achieve a favourable outcome. Benzodiazepines such as lorazepam and diazepam, electroconvulsive therapy, and N-methyl-d-aspartate antagonists such as amantadine and memantine, are the cornerstones of catatonia therapy. In addition, dopamine-modulating second-generation antipsychotics (for example, clozapine and aripiprazole) are effective in some patient populations. Early and appropriate treatment combined with new screening assessments has the potential to reduce the high morbidity and mortality associated with catatonia in psychiatric and non-psychiatric settings.
Gesehen am 27.02.2025